2003
DOI: 10.1177/089270503033340
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Maleated and Acrylic Acid-Functionalized Polyolefin Coupling Agents for HDPE-Wood-Flour Composites

Abstract: The performance of fiber reinforced thermoplastic composites strongly depends on solid fiber-matrix adhesion to allow stress transfer between the phases. Fiber surface modification with coupling agents is generally needed to induce bond formation between the fiber and the polymer. This study investigated the effects of coupling agent's functional monomer (acrylic acid vs. maleic anhydride) and base resin (polyethylene (PE) vs. polypropylene (PP)) types on the tensile and flexural properties of high-density pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
52
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(64 citation statements)
references
References 24 publications
(80 reference statements)
5
52
0
Order By: Relevance
“…Stiffness is completely independent of the presence or absence and also of the amount of the functionalized polymer (not shown). This result agrees well with some literature sources claiming that the presence of maleinated PP does not influence stiffness [3,17,27], although others found some effect on flexural modulus [17,27]. Literature references and our previous experience also showed that stiffness is less sensitive to changes in interfacial interactions than properties measured at larger deformations [41].…”
Section: Propertiessupporting
confidence: 81%
See 2 more Smart Citations
“…Stiffness is completely independent of the presence or absence and also of the amount of the functionalized polymer (not shown). This result agrees well with some literature sources claiming that the presence of maleinated PP does not influence stiffness [3,17,27], although others found some effect on flexural modulus [17,27]. Literature references and our previous experience also showed that stiffness is less sensitive to changes in interfacial interactions than properties measured at larger deformations [41].…”
Section: Propertiessupporting
confidence: 81%
“…The functional groups of these polymers were shown to interact strongly or even react chemically with the surface of wood [17,24,26], while the long alkyl chains diffuse into the matrix making stress transfer possible. The stiffness of the composites is not influenced significantly by the presence of the functionalized polymer [3,17,27], but strength usually increases considerably [2,3,17,19,27,28]. The tensile and flexural strength of polymers usually decreases with increasing filler content in the absence of coupling [2,19,28,31], but the correlation can be turned around and considerable increase can be achieved with the help of functionalized polymers.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…4, E increased as filler loading increased. This finding may be attributed to natural fiber rigidity, which increased the stiffness and reduced the ductility of the composites (Santiagoo et al 2011;Nourbakhsh and Ashori 2008;Li and Matuana 1998;Mohanty et al 2006;. Figure 5 shows the SEM micrographs of untreated (A) and treated (B) kenaf bast at 300× magnification.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Coupling agents are generally used to modify the fiber-matrix interface and thereby enhance the fiber-matrix adhesion. Extensive research work has been carried out on interface modification in natural fiber reinforced composites using external coupling agents [17][18][19][20][21][22][23].…”
Section: Introduction Lmentioning
confidence: 99%